Co-relation between Non-specific Knee Joint Pain and Osteoarthritis - Humagain , M.; Paudel, S; Hengwoju, S (Journal of Institute of Medicine Nepal, 2016)
Introduction: Osteoarthritis (OA) is a degenerative joint disease. Pain is the worst and most frequent problem in OA patients that leads to disability. The rate of knee joint pain has been found to be correlated with OA in many studies. The association of knee pain with OA differs by gender, with advancing age and nature of occupations. Knee radiograph is preferred by most of the physicians for the initial assessment of the knee joint pain. This study was carried out to see the relation between knee joint pain and OA along with age, sex and occupation. Methods: In this prospective cross-sectional study, knee radiographs of 200 patients performed in the Radiology Department of T.U. Teaching Hospital for nonspecific knee joint pain were reviewed. Pain was considered as non specific pain when there was no history of trauma or any known disease affecting the joint and no significant abnormality related to any disease entity was found during clinical examination. The study was conducted over a period of three months between July to September 2015. The proforma was filled and then collected data were analyzed using SPSS software to show the relation between knee joint pain and OA. Results: Among total of 200 knee x-rays, 63% (126) were female and 37% (74) were male. The highest number of population was in the age group of 50-59 year, which comprised 26% of total population and lowest population was in >80 year group comprising 0.5% of total population. Housewives were highest in number comprising 39.5% (79) followed by farmer 19% (38), physical worker 15.5% (31), people in service 12.5% (25), business 7.5% (15) and student 6% (12). Of the total population, 59% (118) had radiographic features of OA changes. Most affected people were older than 50 years and all patients older than 70 years had OA changes. No OA was seen in people younger than 20 years. Highest percentage of OA was found in housewives accounting 51.7% followed by farmers (18.6%) and business people (4.2%. No OA was found in students involved in the study. Conclusion: The study demonstrated that the occurrence of OA is more common finding in population with non-specific knee joint pain. OA is more common in females and population of age ≥50 years. OA is most common in housewives and least in students.